Reconnaissance investigations of magnetic susceptibility of subsoil formation in the selected areas in southern Poland - WOJAS, Anna; ROLIRAT, Anna; GRABOWSKA, Teresa (Geology, Geophysics and Environment, 2010)
In the article, the reconnaissance investigations of the magnetic susceptibility of soils and ochre are presented. Field investigations have been performed in southern Poland; namely in the Łąki Nowohuckie area of Krakow, the eastern surroundings of the city of Trzebinia, and the hamlet of Czerwonki near Rzeszów. Laboratory magnetic analyses have been completed. An increase of soil susceptibility has been observed in the studied areas with high anthropopression (Krakow and Trzebinia). It has been proven that iron particles collected in the soil come from urban-industrial emissions. The higher susceptibility of soils in the Łąki Nowohuckie area, than in the vicinity of Trzebinia, has also been affirmed. The diversity of the low values of soil susceptibility in the Trzebinia area is not connected to the Zn-Pb ores which occurred there. The investigations of ochre susceptibility at Czerwonki Hermanowskie have confirmed its quite strong magnetic properties in comparison with properties of the soil situated in a nearby deposit. The large differentiation of ochre susceptibility has been observed. It is probably connected with the mineral composition of ochre and the processes that occurred in the deposit. The ochre deposit slightly disturbs the geomagnetic field (microanomalies) as is shown on the micromagnetic anomaly map.